1996
DOI: 10.1016/s0022-5223(96)70374-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative tranexamic acid on blood loss after cardiac operations in children

Abstract: Children undergoing cardiac operations in which cardiopulmonary bypass is used are at risk of significant postoperative blood loss. The acquired coagulopathy is complex but is thought to be due, in part, to excessive fibrinolysis. We examined the possibility of reducing postoperative blood loss in children by using the antifibrinolytic drug tranexamic acid. Using a prospective, randomized, double-blind study design, we administered a single dose of tranexamic acid (50 mg/kg intravenously) or saline placebo, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 20 publications
0
49
0
1
Order By: Relevance
“…Of these 142 trials, 95 were apparently randomized, controlled studies. Nine studies were excluded because no clinical outcome other than blood loss was available, [7][8][9][10][11][12][13][14][15] eight studies were found not to be randomized after more thorough analysis, [16][17][18][19][20][21][22][23] five studies concerned cardiac surgery in child- ren, [24][25][26][27][28] and there was one double report. 29,36 66,75,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In addition, 12 studies compared treatment with the conventional dose of aprotinin with lower doses of aprotinin.…”
Section: Literature Search and Methodological Gradingmentioning
confidence: 99%
“…Of these 142 trials, 95 were apparently randomized, controlled studies. Nine studies were excluded because no clinical outcome other than blood loss was available, [7][8][9][10][11][12][13][14][15] eight studies were found not to be randomized after more thorough analysis, [16][17][18][19][20][21][22][23] five studies concerned cardiac surgery in child- ren, [24][25][26][27][28] and there was one double report. 29,36 66,75,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In addition, 12 studies compared treatment with the conventional dose of aprotinin with lower doses of aprotinin.…”
Section: Literature Search and Methodological Gradingmentioning
confidence: 99%
“…4 The use of antifibrinolytic drugs is one of the strategies for reducing blood loss, and tranexamic acid (TA) is among the most commonly administered, especially because the conclusions of the Blood Conservation Using Antifibrinolytics in a Randomized Trial study raised concerns about aprotinin. 5 The efficacy of TA in pediatric cardiac surgery has been demonstrated in several trials [6][7][8][9][10][11] and analyses, 12,13 but the determination of its dosage regimen …”
mentioning
confidence: 99%
“…54 Blood conservation strategies studied for open heart surgery are summarized in Table III. 28,29,[55][56][57][58][59][60][61][62][63] The population studied should be taken into account to interpret published results: age, complexity of surgery, cyanotic/acyanotic disease and reoperations. 1,61 When available, whole blood of less than 48 hr is helpful …”
mentioning
confidence: 99%